2021
DOI: 10.3390/ijerph18041848
|View full text |Cite
|
Sign up to set email alerts
|

Nuts and Older Adults’ Health: A Narrative Review

Abstract: Although the beneficial effects of nuts on cardiometabolic diseases have been well established, little is known about the effects of nuts on age-related diseases. Given that age-related diseases share many biological pathways with cardiometabolic diseases, it is plausible that diets rich in nuts might be beneficial in ameliorating age-related conditions. The objective of this review was to summarise the findings from studies that have examined the associations or effects of nut consumption, either alone or as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…An exception was delayed recall, where significantly higher score was seen with intake greater than 30 g/d. The positive associations between nut intake and cognitive function in this study of relatively healthy older US adults was consistent with previous observational studies that reported significant associations between nut intake and global cognitive function in older adults with or without mild cognitive impairment [ 24 ]. Longitudinal studies also reported that higher nut intake was associated with slower cognitive decline in this population over the study follow-ups [ 23 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An exception was delayed recall, where significantly higher score was seen with intake greater than 30 g/d. The positive associations between nut intake and cognitive function in this study of relatively healthy older US adults was consistent with previous observational studies that reported significant associations between nut intake and global cognitive function in older adults with or without mild cognitive impairment [ 24 ]. Longitudinal studies also reported that higher nut intake was associated with slower cognitive decline in this population over the study follow-ups [ 23 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…It has been proposed that increased nut consumption improves vascular function including endothelial function, arterial compliance, blood pressure and cerebral vascular function, all of which are risk factors that have been implicated in cognitive impairment and dementia [19]. Indeed, there is epidemiological evidence that links nut intake to better cognitive function in older adults [21][22][23][24][25]. Previous reviews have suggested that this positive association between nuts and cognition may be related to the antioxidant properties of nuts [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Several emerging RCTs suggest that almonds may play a role in improving working and visual memory and help to reduce facial wrinkle severity and width. Additionally, emerging data indicates that the intake of nuts such as almonds is associated with improved health status of older adults (e.g., longer telomere length and lower risk of sarcopenia) [116].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…Nuts are rich in unsaturated fatty acids, vitamins, minerals, fiber, and phytochemicals such as polyphenols. There is evidence indicating that nut consumption protects brain health and improves cognitive function, including memory and executive functions [2,3]. A randomized crossover trial carried out by Barbour et al showed an enhancement in cerebrovascular reactivity (defined as the change in cerebral blood flow in response to a vasodilatory or vasoconstrictive stimulus) and cognitive function in healthy overweight middle-aged adults consuming 56e84 g/day of high-oleic peanuts for 12 weeks [4].…”
Section: Introductionmentioning
confidence: 99%